"We know it is not good, but we are constrained": A study on quality of emergency obstetric and newborn care in Northern Ghana. Issue 4 (April 2023) - Ayawine, Alice; Atinga, Roger A.
Abstract: Objective: To explore the quality of emergency obstetric and newborn care provided to newly delivered women in rural Ghana. Methods: A multiple case study design, involving in-depth face to face interviews, was deployed to draw evidence from essential health providers, clients and caretakers. Data were further derived from non-participant observation by means of an observation guide and analysis of physical artifacts using the room-by-room walk-through tool. Data analysis followed Yin's five phase process to case study analysis. Results: Quality of care was compromised by non-adherence to standard practices, inadequate monitoring, crude treatment procedures, lack of basic care needs and poor health providers' relational behaviours. Limited supplies of drugs, equipment and essential care providers further weakened the provision of quality emergency obstetric and newborn care. Conclusion: Inadequate supply of essential logistics and skill gaps on the part of health providers in some maternal and newborn care components adversely produced poor maternal and neonatal outcomes in rural Ghana. Elements of disrespectful care for women suggest violations of their rights in the maternal and newborn care encounter.